Disease progress of apple scab caused by Venturia inaequalis in environmentally friendly growing systems - Holb, I. J. (International Journal of Horticultural Science, 2000)
Progression of apple scab epidemic in six apple cultivars, including two current and susceptible (Gala Must, Elstar), two old (Egri Piros, Darusóvári), and two resistant cultivars (Relinda, Releika), were described and analysed in a two-year-study, in two environmental-friendly growing systems (organic and integrated). Curves of disease progress, linear regression analysis of transformed disease incidence data and Area Under Disease Progress Curves (AUDPC) were used to characterise the epidemic processes of the selected cultivars. Cumulative disease progress curves showed continuous but asymmetrical scab development on the moderate or highly susceptible cultivars Gala Must, Elstar and Egri Piros, and on the tolerant or resistant cultivar Darusóvári and Relinda, in both systems. The cultivar Releika showed no symptoms either on fruit or leaf. In linear regression analysis, the best linearisation was given by logistic transformation. Adequate parameters leaf disease incidence rate, of obtained from a regression equation, were higher in the organic system than in the integrated system. Values of AUDPC showed great differences in leaf disease incidences among cultivars and between growing systems. AUDPC gave more differences for comparison of progresses of disease epidemic than growth rate of disease in different systems of disease control. Moreover, the obtained results were compared with similar studies on different pathosystems, and biological interpretations of the analyses are discussed below.